2018
DOI: 10.1042/bsr20180914
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic roles of circulating ALDH1+ tumor cell in the patients with non-small cell lung cancer

Abstract: Circulating tumor cells can provide important diagnostic and prognostic information of the patients with non-small cell lung cancer (NSCLC). Aldehyde dehydrogenase 1 (ALDH1), a cancer stem cell marker, has been used in various tumors, including NSCLC. In the present study, we isolated the circulating ALDH1+ tumor cells from the NSCLC patients using ALDH1 as a potential marker. Higher percentage of ALDH1+ tumor cells was identified in blood samples from the NSCLC patients compared with normal controls. ALDH1+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The collection of material for biopsy is a rather painful intervention. Notably, prognostic potential of ALDH1 + CTC in patients with BC was suggested in the literature [20][21][22]. ALDH expression by circulating tumor cells correlates with poor clinical outcome, metastatic progression, and the response to therapy in patients with metastatic breast cancer [22].…”
Section: Resultsmentioning
confidence: 99%
“…The collection of material for biopsy is a rather painful intervention. Notably, prognostic potential of ALDH1 + CTC in patients with BC was suggested in the literature [20][21][22]. ALDH expression by circulating tumor cells correlates with poor clinical outcome, metastatic progression, and the response to therapy in patients with metastatic breast cancer [22].…”
Section: Resultsmentioning
confidence: 99%
“…Mannoor et al found that SNORD1C was expressed at higher levels in non-small cell lung cancer cells that were ALDH1+ compared to those that were ALDH1- [ 11 ]. ALDH1+ tumor cells are believed to have higher proliferation rates, self-renewal capacity, and tumorigenic potential in vivo , which constitute important causes of cancer recurrence [ 12 , 13 ]. Therefore, SNORD1C may have a driving effect on non-small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Their levels were inversely correlated with serum tumor necrosis factor-related apoptosis-inducing ligand (sTRAIL) levels, which have been associated with a tumor suppressive effect [ 33 ]. In another study, sTRAIL was negatively correlated with ALDH1+ cells, the latter being a different marker which can be used for NSCLC CTSCs characterization [ 34 ].…”
mentioning
confidence: 99%